2009
DOI: 10.2214/ajr.08.1685
|View full text |Cite
|
Sign up to set email alerts
|

MDCT for Suspected Appendicitis: Effect of Reconstruction Section Thickness on Diagnostic Accuracy, Rate of Appendiceal Visualization, and Reader Confidence Using Axial Images

Abstract: In this investigation of contrast-enhanced MDCT of the appendix, visual ization of the appendix and confidence in interpretation of axial images progressively improved with use of thinner reconstruction sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In addition, our examinations were reconstructed with thin slice thicknesses and intervals, the appendiceal visualisation rate and the reader confidence in its diagnosis being both increased with slice thicknesses lower than 5 mm [30]. Second, the examinations were performed without any oral or IV contrast but several studies have reported high diagnostic performance with unenhanced CT as compared with enhanced CT, even for alternative diseases [16,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our examinations were reconstructed with thin slice thicknesses and intervals, the appendiceal visualisation rate and the reader confidence in its diagnosis being both increased with slice thicknesses lower than 5 mm [30]. Second, the examinations were performed without any oral or IV contrast but several studies have reported high diagnostic performance with unenhanced CT as compared with enhanced CT, even for alternative diseases [16,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…No oral or rectal contrast medium was given for opacification of the bowels. NE-LDCT and CE-SDCT images were reconstructed into axial and coronal sections with 3-mm slice thickness and 3-mm intervals due to improved visualization of the appendix with use of thinner slice reconstruction ( 9 ). All images were anonymized before they were sent to a picture archiving communication system (PACS) for investigation.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the appendix, the impact of slice thickness on several factors, including visualization of the appendix, confidence in appendiceal visualization, diagnostic accuracy, and diagnostic confidence in diagnosing appendicitis has been reported for varying CT slice thicknesses. 23 The authors found that the correctness of the diagnosis of appendicitis was not affected by slice thickness using 3 techniques (5 Â 5 mm, 3 Â 3 mm, and 2 Â 1 mm; thickness and interval). However, progressively thinner section thickness was found to be associated with significant increases in the rate of appendiceal visualization and appendiceal visualization confidence.…”
Section: Image Reconstruction and Post-processingmentioning
confidence: 98%